Dust filter of secondary aluminium industry as raw material of geopolymer foams. (November 2020) - Eliche-Quesada, D.; Ruiz-Molina, S.; Pérez-Villarejo, L.; Castro, E.; Sánchez-Soto, P.J.
Abstract: In this work, the use of waste dust filter of secondary aluminum industry (DFA) to obtain geopolymer foams has been studied. The waste was used as source of alumina and foaming agent. As precursor and principal reactive silica supplier rice husk ash was used. Precursors were chemically activated by means of a sodium hydroxide aqueous solution and a commercial sodium silicate solution. The influence of the DFA content or Si/Al molar ratio (4–7) were determined by keeping the Si/Na molar ratio of 0.7 M constant and the concentration of sodium hydroxide in the activating solution equal to 8.5 M. The geopolymer foams obtained were studied by X-ray Diffraction (XRD), adsorption/desorption of nitrogen, infrared spectroscopy (FTIR), and scanning electron microscope (SEM) techniques. The results indicated that geopolymer foams presented low values of bulk density (643–737 kg/m 3 ) high values of apparent porosity (62–70%), low, but sufficient values of compressive strength (0.5–1.7 MPa) and good values of thermal conductivity (0.131–0.157 W/mK). Lower values of thermal conductivity were obtained for Si/Al = 4 and 5 M ratios, due to the highest apparent porosity and the highest total pore volume. These geopolymer foam materials have similar properties to other construction materials sector such as gypsum boards, foamed concrete, or insulating materials. In addition, its use in other applications of interest such as catalyst support or gas filtration materials could be investigated. Graphical abstract: Image 1 Highlights: Dust filter of secondary aluminium industry waste as source of alumina and foaming agent. Geopolymer foams synthesized from wastes without the presence of other organic foaming agents. Geopolymeric foam characterized by thermal conductivity of less than 0.16 W/mK.